Relações de poder, elites políticas e imprensa no norte do Rio Grande do Sul (1950-1967) - Goulart, Gabriela Tosta (2019)
This dissertation aims to study the relations between the political leadership and the regional press, in the north of Riop Grande do Sul, from 1976 until 1930. It is understood that the press was the supporters’ power for the regional political elite since the Proclmation of the Republic in 1889, advancing the entire Republic Velha’s period until 1930. During this period, 16 newspapers were identified, some of them with short duration and others newspapers that are still active nowadays. This press reported the political clashes and, oftentimes, the press had the objective of being a spokesman for the regional politicians. Thus, found a true identity established between the politics and the press. The most emblematic newspapers cases were both A Voz da Serra and O Nacional. A Voz da Serra, founded in 1916, linked to the Partido Republicano Riograndense’s (PRR) cause by ideological link between the newspaper’s owner and the regional leader Nicolau Araujo Vergueiro. O Nacional was founded in 1925 by both of the two sons of the coronel Gervasio Lucas Annes, political figure who dictated the PRR’s hegemony under Nationwide and he oriented a big part press of the city. Gervasio Lucas Annes built a leadership political identity and he left, as successor, Nicolau Araujo Vergueiro, therefore, the proposed analyses in this research is considering the press importance in maintaining the domination of the PRR in the region from a state context that was permeated by two civil wars. The Revolução Federalista, in 1893, that opposed maragatos and pica-paus and Revolução de 1923, that shook the PRR’s hegemony and demonstrated that the partisan political opposition could only manifest themselves by the revolutionary means. In this sense, the power’s maintenance of the PRR in regional ambit suffered contestation and the press was one of the supporters for the viability domain of the castilhismo-borgismo in the period in question.